Laser finishing in manufacturing of denim garments - Nemeša Ineta (Tekstilna industrija, 2019)
Laser finishing is one of the methods which combined with other traditional denim finishing methods gives the best quality to ready denim garments. Changing process parameters different level and shape material degradations are created to obtain visual look and touch of long time worn clothing. During the last time period traditional denim finishing methods are used to get the main effects and soft touch of the material, while by help of laser finishing dipper degradations of smaller size are created. On the bases of productivity, which depends on laser power and dimensions and movement principles of the work surface, laser finishing equipment can be divided in several groups: shop lasers, laser equipment for small and medium orders, laser equipment for medium and large orders and laser equipment for large production orders.